2021
DOI: 10.1108/jhti-07-2021-0171
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of gastronomic experience affecting on sharing experience: place attachment as a mediator and length of stay as a moderator

Abstract: PurposeThis paper aims to investigate the impact of gastronomic experience on sharing experiences, as well as place attachment as a mediator and length of stay as a moderator.Design/methodology/approachQuantitative method was used in this study. The paper conducted an online survey from 717 international tourists who visited Phuket, a city of gastronomy.FindingsThe result revealed that four dimensions of gastronomic experience – entertainment, escapist, education and aesthetic – affected sharing experience. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 71 publications
(109 reference statements)
1
11
0
Order By: Relevance
“…Respondents believe INT4 for interaction is more important than INT5, which is less preferred. Such findings indicate that the respondents appreciate interacting with people about their experiences at the destination, like hospitality and attributes (Soonsan and Somkai, 2021). But participating in destination-related promotional activities may seem a bit hectic to them due to the degree of physical presence involved in it.…”
Section: Prioritizing the Ce Dimensions Using Ridit Analysismentioning
confidence: 89%
See 2 more Smart Citations
“…Respondents believe INT4 for interaction is more important than INT5, which is less preferred. Such findings indicate that the respondents appreciate interacting with people about their experiences at the destination, like hospitality and attributes (Soonsan and Somkai, 2021). But participating in destination-related promotional activities may seem a bit hectic to them due to the degree of physical presence involved in it.…”
Section: Prioritizing the Ce Dimensions Using Ridit Analysismentioning
confidence: 89%
“…The functional aspects of a tourism destination, such as cost-leadership or service quality, are considered significant by tourists when deciding on a destination (Bhattacharya and Kumar, 2017). With a growing number of travel destinations, tourists have several options to choose from, further increasing the competition among the destinations (Soosan and Somkai, 2021; Arica et al , 2021). Therefore, marketing-mix decisions for a tourism destination must be tourist-centric and address CE's dynamism to optimize destination performance and sustain the competitive advantage (So et al , 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, today it has grown beyond just a need for survival to include the need to enhance the holiday experience (Adongo, Anuga, & Dayour, 2015). Scientific research has also shown that food tourism is a means for tourists to participate and discover the geography and culture of destinations other than the familiar (Lin, Marine-Roig, & Llonch-Molina, 2022;Soonsan & Somkai, 2021). de Jong and Varley (2018) divide gastronomic tourism research into two broad areas: (1) gastronomic heritage, where aspects of cultural, local community opinion and food festivals are pursued, and (2) gastronomic experiences, where aspects connected with tourists' attraction are linked with the destination's gastronomy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Phuket housed regional food capitals, most notably the geographic indication item such as Phuket pineapple products. In recent years, as a result of its efforts to preserve the authenticity and creativity of Thai cuisine, Phuket's gastronomic city has risen to prominence as one of Thailand's most popular gastronomic tourism destinations (Chaiyasain, 2020; Soonsan and Somkai, 2021).…”
Section: Introductionmentioning
confidence: 99%